How is the carbon and oxygen isotope composition of foraminiferal tests influenced by methane seepage? - Bruvik, Kine Liland (UiT Norges arktiske universitet, 2019)
The focus of this thesis is how methane seepage influences foraminifera l tests. Specifically, How how carbon and oxygen isotopes in planktic foraminifera tests are influenced by methane seepage. The study area is Vestnesa Ridge were four gravity cores were collected during a CAGE cruise in 2013. The cores were taken both from the southern side, where flares has have been recorded, and from the northern side, where there are no active seepage areas. The cores were worked on in the lab, samples were taken and sieved. After this were planktic (Neogloboquadrina pachyderma s/d) and benthic (Cassidulina neoteretis) foraminifera were picked. Isotope analyses were done on From the planktic (Neogloboquadrina pachyderma s/d) foraminifera were an isotope analysis done, providing the carbon (δ13C) and oxygen (δ18O) isotope measurements. These values were used to identify if methane seepage had affected the cores. Two of the four cores indicted methane seepage (HH-13-197 and HH-13-215) indicated methane seepage. Both the distinctly negative δ13C and the magnetic susceptibility data indicated methane seepage for these two cores. The isotope signals were used to identify past SMTZ, while the present SMTZ were found in core HH-13-197 from pore water data showing sulphate measurements.